2022
DOI: 10.1177/00469580221095822
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Prostate Cancer: Self-Reported Knowledge and Attitude of Physicians in Jordan

Abstract: Prostate cancer (PC) screening aims to detect PC in early stages, amenable to curative treatment and reduction in disease morbidity and mortality. However, PC screening may be associated with overdiagnosis and complications of unnecessary treatment for indolent disease. Therefore, careful patient selection for PC screening is critical to avoid overestimation and missed diagnosis. The aim of this study was to assess physicians’ knowledge and attitude towards early detection of PC in Jordan and whether their kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Family history, advanced age, and race/ethnicity (ie, African ancestry) are among the known risk factors for Pca [ 36 ]. Approximately one-half of participants (51.65 %) knew at least one risk factor for Pca; of these, 50 % identified advanced age as a risk factor, which is consistent with previous studies that noted significant awareness of age as a risk factor [ [37] , [38] , [39] , [40] ]. However, lower levels of awareness of advanced age as a risk factor have been found in Uganda and elsewhere [ 18 , 35 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Family history, advanced age, and race/ethnicity (ie, African ancestry) are among the known risk factors for Pca [ 36 ]. Approximately one-half of participants (51.65 %) knew at least one risk factor for Pca; of these, 50 % identified advanced age as a risk factor, which is consistent with previous studies that noted significant awareness of age as a risk factor [ [37] , [38] , [39] , [40] ]. However, lower levels of awareness of advanced age as a risk factor have been found in Uganda and elsewhere [ 18 , 35 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
“…Alqudah et al, in their study of clinicians in Jordan, reported that approximately 76 % of the participants were aware of familial predisposition to Pca, and 66 % knew of the association with race/ethnicity [ 38 ]. Similarly, 35.1 % of South African men reported knowing that family history is a risk factor for Pca development [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, scientific education targeting medical personnel, especially non-urologists, should be at the forefront. Furthermore, studies have shown that physicians are one of the essential sources of knowledge about PCa screening in the population ( 17 ), and a more significant proportion of those who have received PSA screening are recommended by physicians ( 15 ), it indicates physicians' recommendations are essential factors in promoting PSA screening behaviors ( 23 ). Thus, it is crucial for medical personnel, especially non-urologists, to master prostate cancer prevention knowledge and to publicize it to accessible men < 40 years old or at risk.…”
Section: Discussionmentioning
confidence: 99%